Peningkatan Hasil Belajar Siswa dalam Pembelajaran Tematik Muatan Terpadu Bahasa Indonesia melalui Metode Picture and Picture Pada Tema 2 Subtema Keluarga - Rohana Rohana (Journal of Classroom Action Research, 2023)
The purpose of this study was to improve student learning outcomes in integrated content thematic learning of Indonesian through the picture and picture method on the theme of 2 sub-themes of the family. This research is a Classroom Action Research (PTK) with 2 cycles, namely cycle I and Cycle II. Each cycle consists of planning, implementing, observing, and reflecting. The subjects of this study were all 31 students in class I-B SD Negeri 2 Labuhan Sumbawa for the academic year 2019/2020, with details of 12 male students and 19 female students. Data analysis in this study will be carried out through several stages, namely by presenting data and drawing conclusions. The indicator of the implementation of this learning is determined by the completeness score of 75% and the maximum score obtained is 100%. The results showed that the Classroom Action Research entitled "Improvement of Student Learning Outcomes in Indonesian Language Integrated Thematic Learning through the Picture and Picture Method in Theme 2 Family Subtheme in Class I-B SD Negeri 2 Labuhan Sumbawa Odd Semester 2019/2020 Academic Year", in terms of this shows an increase in the average learning outcomes of each aspect during cycle I and cycle II. The learning outcomes in the first cycle reached 74.91% KKM, while in the second cycle it reached 87.10%. Student activity in learning in cycle I with an average percentage of 61.83% was sufficient and experienced an increase in activity in cycle II reaching an average percentage of 79.52% in good criteria